Ancestral and neo‐sex chromosomes contribute to population divergence in a dioecious plant. (19th December 2019) - Beaudry, Felix E.G.; Barrett, Spencer C.H.; Wright, Stephen I.
Abstract: Empirical evidence from several animal groups suggests sex chromosomes disproportionately contribute to reproductive isolation. This effect may be enhanced when sex chromosomes are associated with turnover of sex determination systems resulting from structural rearrangements to the chromosomes. We investigated these predictions in the dioecious plant Rumex hastatulus, which is composed of populations of two different sex chromosome cytotypes caused by an X‐autosome fusion. Using population genomic analyses, we investigated the demographic history of R. hastatulus and explored the contributions of ancestral and neo‐sex chromosomes to population genetic divergence. Our study revealed that the cytotypes represent genetically divergent populations with evidence for historical but not contemporary gene flow between them. In agreement with classical predictions, we found that the ancestral X chromosome was disproportionately divergent compared with the rest of the genome. Excess differentiation was also observed on the Y chromosome, even when we used measures of differentiation that control for differences in effective population size. Our estimates of the timing of the origin of neo‐sex chromosomes in R. hastatulus are coincident with cessation of gene flow, suggesting that the chromosomal fusion event that gave rise to the origin of the XYY cytotype may have also contributed to reproductive isolation.